2011
DOI: 10.4049/jimmunol.1002579
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1, a Novel Glucocorticoid Receptor Agonist of Plant Origin, Maintains Glucocorticoid Efficacy with Reduced Side Effects

Abstract: Glucocorticoids (GCs) are widely used to treat inflammatory diseases. However, they cause debilitating side effects, which limit the use of these compounds. In the past decade, many researchers have attempted to find so-called dissociated GCs that have separate distinct transactivation and transrepression activities. Anti-inflammation of GCs is a result of glucocorticoid receptor (GR)-mediated transactivation and transrepression in some tissues, similar to their side effects; therefore, the goal to discover a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 60 publications
5
91
1
Order By: Relevance
“…Studies have also shown that the ligand-activated glucocorticoid receptor is essential for the negative regulation of EGFR signaling (Zhang et al, 2007;Lauriola et al, 2014). In fact, studies have indicated that Rg1 is a functional ligand of the glucocorticoid receptor (Lee et al, 1997;Du et al, 2011). These findings also suggest the notion that Rg1 might activate the glucocorticoid receptor, which may result in the inhibition of EGFR activation.…”
Section: Discussionsupporting
confidence: 52%
“…Studies have also shown that the ligand-activated glucocorticoid receptor is essential for the negative regulation of EGFR signaling (Zhang et al, 2007;Lauriola et al, 2014). In fact, studies have indicated that Rg1 is a functional ligand of the glucocorticoid receptor (Lee et al, 1997;Du et al, 2011). These findings also suggest the notion that Rg1 might activate the glucocorticoid receptor, which may result in the inhibition of EGFR activation.…”
Section: Discussionsupporting
confidence: 52%
“…Total protein was extracted as previously described (16). Briefly, the cells were lysed with RIPA lysis buffer (Beyotime, Haimen, Jiangsu, China) and then centrifuged at 12,000 x g for 15 min at 4˚C.…”
Section: Methodsmentioning
confidence: 99%
“…Ginseng, the root of Panax ginseng CA Meyer, has been a key component in traditional Chinese medicine for more than 1000 years [14] . The traditional beneficial effects of ginseng are replenishment of vital energy, longevity and mood elevation [15] .…”
Section: Introductionmentioning
confidence: 99%
“…The traditional beneficial effects of ginseng are replenishment of vital energy, longevity and mood elevation [15] . The molecular constituents responsible for the action of ginseng are ginsenosides, among which, Rg1 is the most abundant and active ingredient of P ginseng [14,16] . Several studies have shown that Rg1 or ginseng extract has a liver protective effect [16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%